Andrés Neuman and its short narrative's theory (tale and microrrelato) - Álamo Felices, Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This article that is started with an introduction to the spanish contemporary tale's history and development, tries to do a comparative analysis of the “metaliterarias” ideas that Andrés Neuman does about short narrative and microrrelato. We join that theoretical work to his own narrator's exercise, being based on the stories that show up in the books El que espera (2000) and El último minuto (2001).
Keywords: Andrés Neuman; short narrative